27-GAUGE NEEDLE-ASSISTED TECHNIQUE FOR REPOSITIONING A DISLOCATED INTRAOCULAR LENS - Li, Pei-Hsuan; Tseng, Gow-Lieng; Wu, Shao-Chi; Liou, Shiow-Wen (Retina (Philadelphia, Pa.), 2016)
Several techniques for the reposition of a posterior chamber intraocular lens (IOL) posterior dislocating into the vitreous cavity have been developed. However, most of these methods are complicated or include externalizing part of the IOL from a corneal or scleral wound. We here describe a 27-gauge needle-assisted technique for management of a dislocated posterior chamber IOL. This is a retrospective, noncomparative, interventional case series that discusses the results of 27-gauge needle-assisted reposition of the posterior chamber IOL with transscleral sulcus fixation in 5 consecutive cases with an IOL dislocated into vitreous cavity. These patients underwent IOL reposition with the above-mentioned technique between April 2013 and October 2014 and were followed up for at least two months thereafter. The IOLs of the five cases were stable with proper centrations. The postoperative best-corrected visual acuity ranged from 20/30 to 20/20. The technique of 27-gauge needle-assisted reposition of the posterior chamber IOL with transscleral fixation is effective for reposition of a dislocated IOL. This technique provides good IOL fixation without creating a large corneal wound or scleral flap.